Exploring Mathematical Proofs and Solutions in Higher Education: A Case Study on Real Analysis - Isran, Dodi; Susanta, Agus; Rahimah, Dewi; Syafri, Fatrima Santri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
This exploratory study investigates the teaching and learning of mathematical proofs, specifically focusing on real nalysis proofs, in mathematics education programs at the higher education level in Bengkulu Province. Data were collected through in-depth interviews with lecturers and students, classroom observations, and document analysis of students' assignments. The findings reveal that lecturers employ various teaching strategies, such as active learning, step-by-step explanations, and the use of technology to aid understanding. However, students face significant challenges, including difficulties with abstract thinking, gaps in foundational knowledge, and the complex language of mathematical proofs. Despite these challenges, students reported improvements in their logical reasoning, problem-solving, and self-confidence as they were engaged in the construction mathematical proofs. Classroom observations confirmed that collaborative learning was effective in promoting understanding. Document analysis of students' assignments indicated a range of proficiency levels, with some students struggling to produce clear and logical proofs. The study highlights the importance of mathematical proofs in developing critical thinking skills and analytical abilities. It suggests that more interactive, student-centered teaching methods are necessary to address the challenges students face and improve learning outcomes. These findings provide valuable insights for enhancing teaching practices and supporting students' mastery of mathematical proofs.